Where rape does not exist: tracing the unsettled position of marital rape in South Africa through women's recourse-seeking journeys - Karimakwenda, Nyasha (Department of Public Law, 2019)
Through a feminist and interpretivist lens, this dissertation addresses the present dearth of research on marital rape in contemporary South Africa by exploring contradictory institutional responses to marital rape in legal, policy, and social contexts. Drawing from an array of academic traditions spanning law, the social sciences and the humanities, as well as empirical research with women’s rights organisations undertaken by the author, my research question asks: Since the criminalisation of marital rape in 1993, in what ways is marital rape in South Africa rendered (in)visible in and through the institutions where women seek protection from violence? The dissertation argues that despite the criminalisation of marital rape and an emergent women’s rights consciousness within the law, formal and informal institutions that survivors seek help from are complicit in fostering conditions that allow for marital rape to persist. These hindrances arise in both overt and subtle forms. Concurrently, the dissertation draws out the kinds of circumstances through which marital rape is revealed, acknowledged and addressed within institutional environments. Tracing women’s endeavours to seek protection, the research captures the manner in which Black women are compelled to carry disquieting levels of violence, while also discovering the forms of recourse that eventually do provide them relief. The research findings unearth an interplay of factors that preclude recognition of the scale of sexual violence in marriage, and stifle survivors’ ability to find recourse. Amidst this web of barriers, local women’s rights civil society organisations play a critical role in assisting survivors and bringing the sexual abuse to light. Through the range of local services offered by these organisations, survivors are progressively empowered to enact changes in their lives and find means of freeing themselves from abuse.